CPA Examination: Theory of Accounts. - Zlatkovich, Charles T. (The Accounting Review, 1966)
Abstract The article presents theory problems and their solutions prepared by the Board of Examiners of the U.S. body American Institute of Certified Public Accountants and presented as certified public accountant examination in accounting practice on November 5, 1965. The candidates were required to solve all problems. The suggested time allowances for various problems were also given. Objective type and lengthy questions were given. Students were asked to state the period for recognizing benefits derived from the investment credit. The answer is that either over the life of the asset or in the year of acquisition. Another problem is about the business report of Superior Manufacturing Co. The company has used straight-line method of depreciating its plant assets. Students are given data calculated by the depreciation method to be used for income tax and stockholder reporting. They are asked that whether depreciation charges recover or create funds. The answer to the problem is that the purpose of depreciation accounting, as traditionally stated, is to spread the cost, less salvage, of tangible, long-lived assets used by an entity as an expense over their useful lives in a rational and systematic manner. The primary purpose is allocation of cost and presumed benefit; valuation is secondary. Cost is understood to include original acquisition and installation cost, plus betterments, additions, and extraordinary repairs. It may also include appraised values as in the case of donated fixed assets.